Developing standardized patient assessment data elements for Medicare post‐acute care assessments. Issue 4 (2nd March 2022) - Chen, Emily K.; Edelen, Maria O.; McMullen, Tara; Ahluwalia, Sangeeta C.; Dalton, Sarah E.; Paddock, Susan; Rodriguez, Anthony; Shier, Victoria; Mandl, Stella; Mota, Teresa; Saliba, Debra
Abstract: Background: To support interoperability and care planning across provider types, the Improving Medicare Post‐Acute Care Transformation Act of 2014 (IMPACT Act) requires the submission of standardized patient assessment data using the assessment instruments provided by the Centers for Medicare & Medicaid Services (CMS). CMS was tasked with developing standardized assessment data elements (SADEs) within clinical categories named in the IMPACT Act. Method: We used environmental scans, subject matter expert, and stakeholder input to identify candidate SADEs; tested candidate data elements in alpha testing; revised SADEs and training protocols based on alpha analyses and stakeholder feedback; tested SADEs across post‐acute care (PAC) settings in a national field test that included 3121 patients across 143 home health agencies, inpatient rehabilitation facilities, long‐term care hospitals, and skilled nursing facilities in 14 markets across the United States; and analyzed data and stakeholder input from national testing. Field testing measured the time required for assessment, percent completion, and inter‐rater reliability. We analyzed qualitative feedback from stakeholder focus groups and technical expert panels. We also obtained survey and focus group feedback from data collectors. Results: We developed a mixed‐method, multi‐stakeholder procedure to identify and gather input on SADE for cross‐setting use. This process yielded feasible and reliable SADEs for PAC settings that assess pain, cognitive status, mood, and medication reconciliation. The success of this work depended on working iteratively with diverse stakeholders and providing qualitative as well as quantitative evidence. Conclusions: The procedures applied in this project for developing and adopting SADEs for PAC, as well as the challenges and strategies to overcome challenges, should be considered in future item and quality measure development.